2023
DOI: 10.1002/ecm.1574
|View full text |Cite
|
Sign up to set email alerts
|

Demography and dispersal at a grass‐shrub ecotone: A spatial integral projection model for woody plant encroachment

Abstract: The encroachment of woody plants into grasslands is a global phenomenon with implications for biodiversity and ecosystem function. Understanding and predicting the pace of expansion and the underlying processes that control it are key challenges in the study and management of woody encroachment. Theory from spatial population biology predicts that the occurrence and speed of expansion should depend sensitively on the nature of conspecific density dependence. If fitness is maximized at the low‐density encroachm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 76 publications
(106 reference statements)
0
3
0
Order By: Relevance
“…Considerable effort has been invested in developing remote-sensing approaches to characterizing WPE processes retrospectively [ 8 , 25 , 32 ]. However, less attention has been paid to the more exploratory challenge of anticipating areas with greater or lesser potential for further WPE [ 33 , 34 ]. A notable exception is the work of Donovan, Burnett [ 35 ], who found that WPE from windbreaks was most likely along roadways, and less along other features, suggesting a predictive local nature to WPE, albeit in a different landscape context than that of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable effort has been invested in developing remote-sensing approaches to characterizing WPE processes retrospectively [ 8 , 25 , 32 ]. However, less attention has been paid to the more exploratory challenge of anticipating areas with greater or lesser potential for further WPE [ 33 , 34 ]. A notable exception is the work of Donovan, Burnett [ 35 ], who found that WPE from windbreaks was most likely along roadways, and less along other features, suggesting a predictive local nature to WPE, albeit in a different landscape context than that of this study.…”
Section: Discussionmentioning
confidence: 99%
“…The focal dryland ecosystems, while geographically proximal, are undergoing state transitions over time (Zinnert et al, 2021). Under future climates, we expect the Chihuahuan Desert shrubland to expand to replace Chihuahuan Desert grassland (Caracciolo et al, 2016;D'Odorico et al, 2010;Drees et al, 2023), and Desert grassland to overtake Plains grassland (Chung et al, 2019;Collins et al, 2020).…”
Section: Belowground Dynamics At Ecosystem State Transitionsmentioning
confidence: 99%
“…Shrub expansion triggers major ecosystem changes ( Cannone et al, 2022 ) with positive and negative effects on aboveground vegetation ( Drees et al, 2023 ) and belowground soil ecosystems ( Yannarell et al, 2014 ; Ding et al, 2020 ; Ma et al, 2023 ). However, it remains debatable whether shrub expansion improves or degrades land.…”
Section: Introductionmentioning
confidence: 99%
“…However, it remains debatable whether shrub expansion improves or degrades land. Some studies have shown that shrub expansion should be regarded as a degradation process ( Khazieva et al, 2022 ; Root-Bernstein and Hoag, 2022 ; Qu et al, 2023 ) due to its generally negative effects on biodiversity ( Ding et al, 2020 ; Guo et al, 2022 ; Song and Wang, 2022 ; Gómez-García et al, 2023 ), livestock production ( Eldridge and Ding, 2020 ; Root-Bernstein and Hoag, 2022 ), economy ( Drees et al, 2023 ), and ecosystem functions ( Li et al, 2022b ). Other studies have revealed that shrubs do not have a negative effect on soil quality ( Ambrosino et al, 2023 ) but enhance nutrient cycling, primary production, soil water and nutrients ( Chandregowda et al, 2018 ; Li D. et al, 2023 ), and bacterial diversity ( Guo et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%